Dry Media Synthesis of Novel Pyrrolo-pyrimidines - Mishra, A. D. (Journal of Nepal Chemical Society, 2010)
A series of new 2-thioxo-3,7-disubstituted-5,6-diphenylpyrrolo[2,3-d]pyrimidin-4(1H) -ones have been synthesized by the condensation of 2-amino3-ethylcarboxylate-4,5-diphenyl pyrroles with mono-substituted arylthioureas in dry media under microwave irradiations. All the synthesized compounds were screened for their antifungal and antibacterial activities and found to possess mild to moderate antimicrobial activities. Keywords: Thioureas, Pyrrolo-pyrimidines, Microwave irradiation, Antimicrobial activities. DOI: 10.3126/jncs.v25i0.3306 Journal of Nepal Chemical Society Volume 25, 2010 pp 83-88